Information security breaches avoidance treatment based on ISO27001 - Krausz, Michael (IT Governance Press, 2014)
This book helps you to manage a security breach by detailing what to do as soon as you discover a breach. Be prepared, be prompt, be decisive. When your organisation's security is compromised, you cannot afford to waste time deciding how to resolve the issue. Updated to cover ISO27001:2013, this second edition gives you clear guidance on how to treat an information security breach and tells you the plans and procedures you have to put in place to minimise damage and return to business as usual. A recovery plan will help you to: recover, and resume normal operations, more quickly; preserve customer confidence by quickly resolving service disruption; secure evidence to help with any criminal investigation and improve your chances of catching those responsible. Read this guide and find out how to manage in the face of a data breach. --
Includes bibliographical references. - Online resource; title from title page (Safari, viewed August 9, 2014)
Keywords: Computer security; Hacking; Computer networks -- Security measures; Computer Security; Sécurité informatique; Piratage informatique; Réseaux d'ordinateurs; Sécurité; Mesures; COMPUTERS; Security; General; Computer networks; Security measures